(untitled) (ModaPalavra e-periódico, 2021)
The article investigates the risks involved in retail apparel product development. Due to the complexity of the fashion business due to short production cycles, the subjective variables involved in consumer decision making, and the difficulty in balancing collection attributes, the risks of apparel products not having a satisfactory commercial performance is significant. Thus, the objective of the research was to propose recommendations associated with retail apparel product development to reduce the risks of poor collection performance from the perspective of experts. To this end, an applied research was carried out combining the quantitative and qualitative methods in a single data collection instrument. Theory addressed the main risks of fashion according to Cietta (2017), Kotler, Armstrong and Opresnik (2018), Shaw and Koumbis (2014), among others. The resulting set of recommendations addresses aspects related to the company’s target audience, performance indicators, planning, schedule, and agility, among others. As a product of the research, a visual matrix was presented with the recommendations related to the main risks identified.